2011
DOI: 10.1007/s00530-011-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Personalise your massively multiplayer online game (MMOG) with Artemis

Abstract: Better mobile computing, broadband and devices have contributed to the fast growth and popularity of massively multiplayer online games (MMOGs). Players are now expecting a more personalised gaming experience as personalisation has begun to filter into most games and not just MMOGs. In this paper, we explain how players of MMOGs can enjoy a ubiquitous and personalised gaming experience anywhere, on any device, and on any network with Artemis. MPEG-7 is not traditionally used for modelling games; however, Artem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Team formation is an important but much neglected aspect of collaborative games, yet it is a widely-explored topic in non-gaming domains, such as in collaborative filtering and recommendation (Retna Raj and Sasipraba 2015;Ghenname et al 2015;Najafabadi and Mahrin 2016), collaborative design (Xu et al 2010), collaborative crowdsourcing (Lykourentzou et al 2016), and expert collaboration in social networks (Basiri et al 2017). However, in multi-player games, the focus has overwhelmingly been on player matching and more so with a view to finding worthy opponents for players to play against rather than suitable players to play with in a team (Daylamani Zad et al 2012). For example, Corem et al (2013) propose a technique for quickly matching opponents with similar skill levels to facilitate fair tournaments, while Tsai (2016) propose a technique for matching competitors in educational multi-player online games.…”
Section: Advantages and Challenges Of Collaborative Gamesmentioning
confidence: 99%
“…Team formation is an important but much neglected aspect of collaborative games, yet it is a widely-explored topic in non-gaming domains, such as in collaborative filtering and recommendation (Retna Raj and Sasipraba 2015;Ghenname et al 2015;Najafabadi and Mahrin 2016), collaborative design (Xu et al 2010), collaborative crowdsourcing (Lykourentzou et al 2016), and expert collaboration in social networks (Basiri et al 2017). However, in multi-player games, the focus has overwhelmingly been on player matching and more so with a view to finding worthy opponents for players to play against rather than suitable players to play with in a team (Daylamani Zad et al 2012). For example, Corem et al (2013) propose a technique for quickly matching opponents with similar skill levels to facilitate fair tournaments, while Tsai (2016) propose a technique for matching competitors in educational multi-player online games.…”
Section: Advantages and Challenges Of Collaborative Gamesmentioning
confidence: 99%
“…It builds upon our previous work in collaboration and personalisation in digital games [66,67]. The game connects to the adjustment zone which interacts directly both with the game and the profiling zone.…”
Section: The Lu-lu Add-on Architecturementioning
confidence: 99%
“…Players are now expecting a more personalised gaming experience as personalisation has begun to filter into most games [124]. Research has suggested that game personalisation raises player loyalty and enjoyment, which in turn makes gaming experience a (commercial) success [110,115].…”
Section: Effect On Player Satisfactionmentioning
confidence: 99%